Gender related differences in pressure distribution, pelvis movement and subjective perception during cycling - Richter, S.; Schwanitz, S.; Michel, F. I. (Journal of Science and Cycling, 2023)
This research aims to examine and compare the saddle pressure distribution, pelvis movement and subjective feedback regarding perceived saddle pressure and stability of male and female cyclists. For this corresponding data are recorded after three minutes of sporty cycling. The findings Indicate notable differences, which can be attributed to anatomical variations between genders. These results have practical Implications for the design of saddles and seat pads, as they highlight the need for gender-specific considerations In cycling equipment.